한-중 FTA 활성화를 위한 관세사의 역할 제고 방안 - 최준호(Jun-Ho Choi) (무역연구, 2016)
Korea-China FTA began in December and that by 2015. China's customs have a huge impact on the Korean economy context opens them. The Elimination of tariff item 958. The country is opening up to 80 billion market immediately to ferment. Tariffs are low in the winter. step by step year by year within 10 years and again at 5,846 in the tariffs is the Elimination of the above item. The amount of income as a result of the start of FTA, but there are plentry of steep this FTA is in itself a big Korean economy growing impact. But as a company line the wings of the People's China come pouring in putting their products tariff cuts of the offensive should be against. To take advadvantage of the FTA during a major check points are as follows: HS Code of the goods for export and the import of the HS Code is consistent with the FTA tariff rate based on the origin of the goods for export, check and determine wheather the certificate of origin, meet the FTA related documents. etc., As a result the FTA preference tariff benefit many documents in the content of work and accord the right products and process. must be performed you should get the correct tariff for small and medium sized company consultancy will be given preferential tariff benefits. KCI Citation Count: 3